2022
DOI: 10.3390/gastroent13030024
|View full text |Cite
|
Sign up to set email alerts
|

First Therapeutic Approval for Eosinophilic Esophagitis

Abstract: Eosinophilic esophagitis (EE) is a chronic, immune-mediated or antigen-mediated esophageal disease. Treatment for patients with EE can be challenging with no previously approved medications. Current management strategies follow the four D’s paradigm of drugs, dietary elimination, dilation, and disease anxiety and hypervigilance therapy. On 20 May 2022, dupilumab was approved by FDA for EE. A dose of 300 mg dupilumab weekly significantly improved signs and symptoms of EE compared to placebo in a phase 3 trial. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Yet, these studies were only powered to assess changes in eosinophil counts rather than any clinical outcomes. Only recently (2022) dupilumab, a fully human monoclonal antibody that blocks IL-4 and IL-13 signaling, was approved by the FDA as first target treatment for eosinophilic esophagitis given the improved histologic remission (rates of around 60% when administered weekly vs. 5% in placebo; p < 0.001) and alleviated symptoms of the disease [ 38 , 39 ]. In this context as novel therapies and clinical indications or drug repurposing begin to emerge (i.e., see Table 1 for ongoing clinical trials on the use of benralizumab), there is a growing need for the full characterization and standardization of outcomes to better understand treatment responses and to facilitate the optimization and personalization of treatment [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, these studies were only powered to assess changes in eosinophil counts rather than any clinical outcomes. Only recently (2022) dupilumab, a fully human monoclonal antibody that blocks IL-4 and IL-13 signaling, was approved by the FDA as first target treatment for eosinophilic esophagitis given the improved histologic remission (rates of around 60% when administered weekly vs. 5% in placebo; p < 0.001) and alleviated symptoms of the disease [ 38 , 39 ]. In this context as novel therapies and clinical indications or drug repurposing begin to emerge (i.e., see Table 1 for ongoing clinical trials on the use of benralizumab), there is a growing need for the full characterization and standardization of outcomes to better understand treatment responses and to facilitate the optimization and personalization of treatment [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, so far only the biologic dupilumab has been approved (May 2022) by the US Food and Drug Administration (FDA) agency to treat eosinophilic esophagitis (adults and pediatric patients 12 years and older), grounded on the positive results of a phase 3 randomized, double-blind, multicenter, and placebo-controlled trial [ 38 , 39 ]. Other approvals of biological treatments for these EGID indications are scarce [ 40 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Dupilumab is a human monoclonal antibody that targets the IL-4 receptor alpha chain (IL-4Rα), leading to the inhibition of IgE production, although the most important in factor EoE is Th-2 response inhibition [ 90 ]. It is worth mentioning that dupilumab was approved by the FDA in 2022 as the first drug for EoE treatment in people aged 12 years or older and weighing at least 40 kg [ 91 ]. The recommended dose is 300 mg per week [ 91 ].…”
Section: Treatmentmentioning
confidence: 99%
“…It is worth mentioning that dupilumab was approved by the FDA in 2022 as the first drug for EoE treatment in people aged 12 years or older and weighing at least 40 kg [ 91 ]. The recommended dose is 300 mg per week [ 91 ]. The latest randomized controlled trial on dupilumab showed that the majority of patients taking this drug at a weekly dose of 300 mg had statistically significant improvements in histologic outcomes and reductions in symptoms of eosinophilic esophagitis compared to the placebo [ 92 ].…”
Section: Treatmentmentioning
confidence: 99%
“…4 They have been approved for AD (dupilumab and tralokinumab) as well as for related Type 2 (T2) comorbidities such as allergic asthma, chronic rhinosinusitis with nasal polyps, prurigo nodularis and eosinophilic esophagitis (all dupilumab). 8 Small molecules, with a broader mode of action by targeting the JAK-STAT (Janus kinase/signal transduction and activator of transcription signaling, i.e., down-stream of numerous cytokine receptors) pathways, have been approved in many countries including the US (abrocitinib, upadacitinib) and Europe (baricitinib, abrocitinib, upadacitinib). 5 The most common subtype of psoriasis, PV, is characterized by well-demarcated erythematous plaques with coarse scale.…”
Section: Introductionmentioning
confidence: 99%